Angiopoietin-1 is expressed in the synovium of patients with rheumatoid arthritis and is induced by tumour necrosis factor α. Issue 2 (1st February 2003) - Gravallese, E M; Pettit, A R; Lee, R; Madore, R; Manning, C; Tsay, A; Gaspar, J; Goldring, M B; Goldring, S R; Oettgen, P
Abstract : Objectives: To examine the potential role of the angiogenic growth factor angiopoietin-1 (Ang-1) in inflammatory arthritis. Methods: Eighteen synovial tissue samples were obtained from 17 patients with a clinical diagnosis of rheumatoid arthritis (RA) and compared with six synovial tissue samples from six patients with osteoarthritis (OA). Ang-1 expression in synovial tissues was determined by immunohistochemistry and in situ hybridisation. Ang-1 mRNA and protein expression were also examined by northern blot analysis and enzyme linked immunosorbent assay (ELISA) in cultured synovial fibroblasts and human umbilical vein endothelial cells (HUVECs) before and after treatment with tumour necrosis factor (TNF)α. Results: Ang-1 protein expression was detected by immunohistochemistry in 16/18 RA synovial tissue samples. Ang-1 protein was frequently observed in the synovial lining layer and in cells within the sublining synovial tissue, in both perivascular areas and in areas remote from vessels. In contrast, Ang-1 was only weakly detected in these sites in OA samples. Ang-1 mRNA and protein were also expressed in cultured synovial fibroblasts derived from patients with RA. In addition, induction of Ang-1 mRNA and protein was observed by northern blot analysis and ELISA after stimulation of RA synovial fibroblasts, but not HUVECs, with the proinflammatory cytokine TNFα. Conclusions: Ang-1 mRNA and protein are expressed in the synovium of patients with RA, and are up regulated in synovial fibroblasts by TNFα. Ang-1 may therefore be an important regulator of angiogenesis in inflammatory arthritis.